Do Professional Commitment and Anticipatory Socialization Affect The Intention To Do Whistleblowing? - Claudia Tompunu; Frisky Jeremy Kasingku; Ika Prayantiu (INTERNATIONAL RESEARCH JOURNAL OF BUSINESS STUDIES, 2020)
The corruption in Indonesia is one of the biggest problems the government and the business must face. Employee in the entity may provide one of the solutions for this problem. They may do the whistleblowing when they know that there is violation in the entity. Professional commitment and anticipatory socialization are the factors to foster whistleblowing. This study aims to obtain empirical evidence regarding the impact of professional commitment and anticipatory socialization toward whistleblowing intention. 155 eligible accounting students are taken as subjects for this study. The questionnaire is disseminated electronically to the sample. As a result, professional commitment affects whistleblowing intentions of accounting students. Furthermore, male who profess professional commitment will likely do the action of whistleblowing compare to female. On the other hand, there is no statistical evidence found to prove that anticipatory socialization affects the intention to do whistleblowing. Consequently, the system of the company must facilitate the improvement of professional commitment so it may foster the intention of the employees to whistleblow. Therefore, manager should pay attention to degree of the professional commitment of the employees.Keywords: Anticipatory socialization, Professional commitment, Whistleblowing* PT Triputra Energi Megatara, Menara Kadin Indonesia Lt. 20, Jl. H. R. Rasuna Said Kav. 2&3, Setia Budi, Jakarta, 12950** Departement of Economics and Business, Universitas Klabat, Jl. Arnold Mononutu, Airmadidi Bawah, Kec. Airmadidi, Kabupaten Minahasa Utara, Sulawesi Utara 95371 https://doi.org/10.21632/irjbs.13.3.241-248